ENHANCING LOCAL ECONOMIC THROUGH RURAL TOURISM : CASE STUDY CISEENG VILLAGE - liliana Dewi; Ika Suryono Djunaid (Universitas Djuanda Bogor, 2019)
Five aspects in the development have been observed namely transportation, accommodation, food and beverage facilities, tourist attraction, souvenir. This study use qualitative study approach. The data used are primary and secondary data collected in several ways including observation, interviews, documentation and literature. This study focusing on identify potency of Ciseeng village, business opportunity and employment and marketing strategy to enhance local economy. Result show that there is open wide opportunity for Ciseeng village to enhance local economy through rural tourism, operated and managed by community. Motivation and commitment to learn and to grow are needed in this community. This study was conducted with the aim of giving input and encouraging creativity to the local community, the Government of Bogor Regency, the Tourism Local Community Leader to enhance local economy.